Intensive cyanidation of a gold concentrate - Azañero Ortiz, Angel (2000)
The need arises to take advantage of the best way to increase the added value of our mining products, specifically concentrates containing precious metals, to obtain maximum economic benefit. A method is formulated to determine optimal conditions for leaching concentrates. This method is fundamentally based on cyaniding gold concentrates that respond efficiently to this process, then developing alternatives for the recovery of Au and Ag from pregnant solutions, using the known methods of carbon in pulp and merrill crowe or another that consists of selectively precipitating silver with sodium sulfide and from the remaining solution, recover the gold with activated carbon, efficiently obtaining high quality separate products.